Fiber optic measurement techniques - Hui, Rongqing (Elsevier/Academic Press, 2009)
Fiber Optic Measurement Techniques is an indispensable collection of key optical measurement techniques essential for developing and characterizing today's photonic devices and fiber optic systems. The book gives comprehensive and systematic descriptions of various fiber optic measurement methods with the emphasis on the understanding of optoelectronic signal processing methodologies, helping the reader to weigh up the pros and cons of each technique and establish their suitability for the task at hand. Carefully balancing descriptions of principle, operations and optoelectronic circuit implementation, this indispensable resource will enable the engineer to: Understand the implications of various measurement results and system performance qualifications; Characterize modern optical systems and devices; Select optical devices and subsystems in optical network design and implementation; Design innovative instrumentations for fiber optic systems. This book brings together in one volume the fundamental principles with the latest techniques, making it a complete resource for the optical and communications engineer developing future optical devices and fiber optic systems. Optical fiber communication systems and networks constitute the core of the telecom infrastructure of the information society worldwide.
Keywords: Fiber optics -- Measurement.; Optoelectronic devices.; Optical fibers.; elektronické knihy; electronic books